TECHNOLOGY OF GOGO RICE CULTURE IN WEST KALIMANTAN, SANGGAU REGENCY (Case Study in Kecamatan Balai) - Sution Sution (Agros Journal of Agriculture Science, 2017)
Productivity of upland rice in West Kalimantan is not optimal 1.88 ton ha-1. Upland rice productivity is still low due to cultivation technology is not maximized. Purpose of study to obtain upland rice cultivation technology appropriate to produce optimal plant productivity. Research conducted with survey in village of Bulu Bala, Empirang, and Makawing, in January up to March 2015. Location determination done by purposive sampling to select areas gogo rice centra, then randomly selected respondents in each village 20. Results showed that land clearing is done manually, slash and burn. Planting is done by way of drill, plant spacing is irregular, number of seeds per hole 5-10 seed per hole, used local varieties, has a long life of five up to six months. Cropping pattern intercropping with vegetables, other crops and plantation crops. Rotation of upland rice made with rubber and oil palm. Manually weed control, fertilization and pest control is rarely done. Harvest is done using crab and sequence, grain is threshed by way of “girik”, grain dried and carried out storage of rice in the granary.